Exploring the Influence of Company Growth, Leverage, Market Capitalization, and Profitability on Corporate Social Responsibility Disclosure - Astrawan, I Kadek Yogi; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi, 2025)
Corporate Social Responsibility (CSR) disclosure represents the communication between a company and the public regarding its activities that impact social, environmental, and economic aspects of society. This research aims to examine the influence of company growth, leverage, market capitalization, and profitability on CSR disclosure among healthcare sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The study's sample consists of 16 companies, yielding a total of 61 observations. A non-probability sampling method, specifically purposive sampling, was employed to select the sample. The analysis technique applied in this research is multiple linear regression. The results indicate that company growth and leverage do not significantly affect CSR disclosure, whereas market capitalization and profitability have a positive influence on CSR disclosure. Keywords: Company Growth; Leverage; Market Capitalization; Profitability; CSR Disclosure.